RELATIVE EFFECT OF COVID-19 ON TEACHING AND LEARNING IN HIGHER INSTITUTIONS IN EKITI STATE, NIGERIA - Ibitola, Makinde; Olurotimi, Ogunlade; Oluwatoyin, Omotoyinbo (American Journal of Education and Practice, 2021)
Purpose: This study was conducted to examine the impact of COVID-19 on students' academic calendar of higher institutions in Ekiti State, Nigeria. Methodology: The study adopted descriptive survey research design guided by two research questions which were formulated to guide the study. Questionnaire was used for data collection Random sampling technique was used to select the population size. Also one and hundred fifty (150) questionnaire instruments were administered to the respondents who formed the population of the study through email. The questionnaires were filled and returned to the researcher and data collected was presented in percentage tables. Findings: The study revealed among others that COVID-19 schools close down has affected the academic calendar of schools in Nigeria because major external examinations would be postponed. Also, COVID-19 schools close down has led to suspension of teaching and learning, and suspension of all extra-curriculum activities in higher institutions. Recommendations: Based on the findings of the study, recommendations were made. The schools administrators should ensure teachers develop strategies to cover all their scheme of work for the term before going for internal examinations, the government should provide all infrastructural facilities that will support online education in all the schools in Ekiti State to prevent any eventuality of future close down of schools because of pandemic